Description Of Officers' Behavior In Implementing Security And Confidentiality Of Electronic Medical Record Data In UKRM at XX Hospital - MUHAMMAD RASHIF ANSHARI; Galih Persadha (UrbanGreen, 2026)
Electronic Medical Records (EMR) play an important role in improving the efficiency and quality of healthcare services. However, the implementation of EMR also introduces risks related to data security and patient confidentiality, requiring proper user behavior in accordance with information security principles. This study aimed to describe staff behavior in implementing EMR data security and confidentiality at Islamic Hospital Banjarmasin based on the Confidentiality, Integrity, and Availability (CIA) principles. This study employed a descriptive quantitative method with a cross-sectional design. The population and sample consisted of 20 EMR users, including healthcare service staff and IT personnel, selected using a total sampling technique. Data were collected through a Likert-scale questionnaire and analyzed descriptively using frequency distribution and percentage calculations. The results showed that staff behavior in implementing EMR security and confidentiality was categorized as very high, with an overall percentage of 89.53%. The Integrity dimension obtained the highest score (93.96%), followed by Confidentiality (91.15%) and Availability (85.34%). Although all dimensions were categorized as very high, several weaknesses were still identified, including irregular password changes, inconsistent logout practices, and limited information security training. The study concluded that EMR security and confidentiality implementation at Islamic Hospital Banjarmasin had been conducted very well. However, improvements are still needed in user discipline and information security reinforcement